Internet finance and its potential risks: the case of China - Tian, Zhongkai; Sheikh Hassan, Ahmad Fahmi (Academic Inspired Network, 2019)
Internet finance is a global phenomenon that further close the digital divide and sidelining of small-medium enterprise (SMEs) equipping for a fourth industrial revolution market. This study reviews the development of Internet finance in China deemed to be the largest Internet finance market in the world. The extant of literature and market reports suggest that this overwhelming performance of China Internet financing is due to factors such as financial market gap, popularity of third-party payment and high returns. However, against mthe traditional financing operations, investors in this sector suffer substantial degree of risks due to fraud leading to huge losses. We argue that there needs a concerted effort by government and oversight bodies to improve market disciplines to ensure a healthy development of this alternative financing thereby enhancing the economy development of China and elsewhere where Internet financing is operating.